An (un)happy marriage: child psychotherapy with children who are medicated for ADHD. Issue 1 (2nd January 2021) - Peter, Sarah
ABSTRACT: Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common psychiatric diagnoses given in childhood. The recommended treatment is medication in combination with behavioural intervention, and psychoanalytic treatments are rarely recommended or sought. However, in recent decades, there has been an increase in psychoanalytic interest in ADHD, conceptualising it as a complex, biopsychosocial phenomenon requiring a multimodal approach, and suggesting that psychoanalytic psychotherapy can be helpfully and effectively combined with medication in treatment. This study aimed to empirically investigate this practice, by interviewing psychoanalytic child psychotherapists about their experiences of treating children medicated for ADHD. Semi-structured interviews were carried out with six child psychotherapists. The data were analysed qualitatively, using thematic analysis and discourse analysis. Participants presented psychotherapy and medication as theoretically compatible and complementary, but expressed uncertainty about and resistance to the use of medication alongside psychotherapy in practice. Interviewees adopted positions of compliance, avoidance and resistance to the practice of combining medication and psychotherapy, understood as negotiations of the powerful medical discourse of ADHD. While the literature emphasises the potential for psychopharmacological and psychoanalytic approaches to be mutually enriching, this study highlights the challenges of adopting a multi-perspective approach in this contested field.